Effect of filling technique on the bond strength of methacrylate and silorane-based composite restorations - Fernanda Weingartner MACHADO; Fernanda Blos BORGES; Maximiliano Sérgio CENCI; Rafael Ratto de MORAES; Noéli BOSCATO (Brazilian Oral Research, 2016)
Abstract The bond strength of methacrylate (Z350, 3M ESPE) and silorane (P90, 3M ESPE) restorations, using different cavity filling techniques, was investigated. Cavities (6 × 3 × 3) in bovine teeth were filled using bulk, oblique, or horizontal increments. A push-out test was carried out after 24 h. Data were statistically analyzed (α = 5%). Methacrylate-based composites and the horizontal filling technique showed the highest bond strength values (10.2 ± 3.9, p < 0.05). Silorane-based composites showed no statistically significant differences regarding the filling techniques (p > 0.05).